Artificial Human Optimization-An Introduction - Gajawada, Satish (Transactions on Engineering and Computing Sciences, 2018)
The goal of this article is : 1) To popularize "Artificial Human Optimization" field 2) To show opportunities that exist in "Artificial Human Optimization" field. 3) To Design an optimization method based on Artificial Humans 4) To show reviews of papers in “Artificial Human Optimization” field 5) To make corrections to my previews work in “Artificial Human Optimization” field 6) To encourage researchers across the globe to work in “Artificial Human Optimization” field 7) To give Artificial Human Optimization award to researchers who contributed to this new field